Saving Shiloh - Tung, Sandy; Wilson, Scott, 1942-; Dolley, Jason; Dowd, Ann.; Gorgoni, Adam.; Naylor, Phyllis Reynolds; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
Is ornery Judd Travers a changed man? Marty believes he is, even when a body is found and just about everyone in town thinks Judd is the murderer. But the piece of orange cloth Shiloh digs up may be a clue to what really happened.
English track: Dolby digital 5.1.
Spanish track: Dolby digital 2.0.
Title from container.
Based on the novel by Phyllis Reynolds Naylor.
Special features: interviews with cast and filmmakers; 'Open your heart' music video; 'An interview with Shiloh'.
Director of photography, Lex DuPont ; editor, Clarinda Wong ; music, Adam Gorgoni ; costume designer, Joslyn Lawrence ; production designer, Cat Cacciatore.
Keywords: Murder -- Drama; Evidence -- Drama; Children's films; Detective and mystery films; Feature films; Suspense films